Bullous variant of familial biphasic lichen amyloidosis: A unique combination of three rare presentations - Vijayalaxmi Veerabasappa Suranagi; B S Siddramappa; Hema Basappa Bannur; Prakash V Patil; Reshma S Davangeri (Wolters Kluwer Medknow Publications, 2015)
A 55-year-old man presented with multiple, itchy papules and macules on the trunk and extremities. Histopathologic examination of biopsy specimens taken from three different lesions showed a subepidermal blister with amyloid deposits in the dermal papillae. No systemic disease or involvement of other organs was detected. The clinical and histological findings were compatible with a bullous variant of lichen amyloidosis (LA). Primary cutaneous localized amyloidosis usually presents with papular, macular or nodular lesions. Bullous lesions associated with LA are very rare. Furthermore, patient had seven other members in the family with similar lesions, which is also a rare occurrence. We report a case with a rare combination of biphasic, bullous variant of familial LA.